Diabetes mellitus as a risk factor for open-angle glaucoma: a systematic review and meta-analysis. - Minwen Zhou; Wei Wang; Wenbin Huang; Xiulan Zhang (PLoS ONE)
Objective To determine the association between diabetes mellitus (DM) and primary open-angle glaucoma (POAG). Methods This is a systematic review and meta-analysis of case-control and cohort studies. The literature search included two databases (PubMed and Embase) and the reference lists of the retrieved studies. Separate meta-analyses for case-control studies and cohort studies were conducted using random-effects models, with results reported as adjusted odds ratios (ORs) and relative risks (RRs), respectively. Results Thirteen studies--seven case-control studies and six population-based cohort studies--were included in this meta-analysis. The pooled RR of the association between DM and POAG based on the risk estimates of the six cohort studies was 1.40 (95% CI, 1.25-1.57). The pooled OR of the association between DM and POAG based on the risk estimates of the seven case-control studies was 1.49 (95% CI, 1.17-1.88). There was considerable heterogeneity among the case-control studies that reported an association between DM mellitus and POAG (P<0.001) and no significant heterogeneity among the cohort studies (P = 0.377). After omitting the case-control study that contributed significantly to the heterogeneity, the pooled OR for the association between DM and POAG was 1.35 (95% CI, 1.06-1.74). Conclusions Individuals with DM have an increased risk of developing POAG.